Analysis of Job Value-Based Compensation System Implementation on MSME PT Baneex Indonesia - Imam Firdaus Nugroho; Alief Ibadurrahman; Tubagus Yopi Ramadhan; Dhafa Adriansyah; Fadhil Utama H (Ridwan Institute, 2022)
One of the most significant contributors to the economy in the Republic of Indonesia is SMEs. SMEs are a pretty good means for forming and providing employment opportunities. There must be someone who has an entrepreneurial spirit and empathy for their environment in environment. SMEs are one of the actual evidence of the nation's economic development from educated people who want income and help people around them by creating jobs. Small and Medium Enterprises (SMEs) have an excellent opportunity to become a pillar of the people's economy. SMEs can be a good forum for job creation, with an average contribution to Indonesia's Gross Domestic Product (GDP) of 50% in the last three years. For a business to run correctly and adequately, work management is needed to regulate the rights and obligations of employers and workers. Entrepreneurs have the right to get income from their business, not apart from their obligation to pay for the hard work of their employees. Workers or employees have the right to be rewarded for their obligations, namely work. For a harmonious relationship for both parties, both employers and workers, good management of employees is required, including the payment of wages or salaries. Decent wages for workers can make them comfortable in a job and give their best effort. Compensation management is developing and implementing strategies, policies, and compensation systems that help an organization achieve its goals by obtaining and retaining the necessary people and increasing their motivation and commitment. The purpose of the establishment of compensation management is to respect employee performance, ensure fairness of employee salaries, retain employees or reduce employee turnover, obtain quality employees, control costs, and comply with regulations. Considerations regarding compensation management include pay for position, pay for a person, and pay for performance.